Formulasi Sediaan Masker Gel Peel-Off Ekstrak Wortel (Daucus carota L.) dengan Variasi Konsentrasi PVA (Polyvinyl Alcohol) Sebagai Gelling Agent - Cut Suraiya Wahyuni Utami; Resmila Dewi; Erda Marnizar; Widya Angreni (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Carrots (Daucus carota L.) can be utilized as raw material for cosmetic preparations. Carrots contain many chemical compounds such as β-carotene and provitamin A. In addition to high provitamin A content, carrots also contain vitamin C, vitamin K, fiber, protein, carbohydrates, and fat. This research aims to formulate carrot extract in a peel-off mask gel preparation. The peel-off mask gel formulation was made with variations in PVA concentration, namely 0% (FI); 2.5% (FII); 5% (FIII) and 7.5% (FIV). Evaluation of peel-off mask gel preparation includes organoleptic, homogeneity, pH, spreadability, drying time, irritation test and liking test. The results showed that all formulas of peel-off mask gel preparations had met the requirements in terms of organoleptic aspects, homogeneity, spreadability, and drying time and did not irritate the skin so it was safe to use. Carrot extract can be formulated in peel-off mask gel preparation and the best preparation formula is F IV with 7.5% PVA concentration.